In Vitro and In Vivo Behaviour of Four Different 99(m)Tc-HEDP Complexes - Inoue, O.; Yamaguchi, T.; Ikeda, I. (Nuklearmedizin - NuclearMedicine, 1982)
According to absorption spectra, at least four different 99Tc-HEDP complexes [complex I (colorless), complex II (yellow), complex III (pink-red) and complex IV (brown)] were observed under various labeling conditions. Both pH and Sn (II)-HEDP concentration greatly influenced the formation of these complexes. In acidic or neutral media, complex II was the main product while in alkaline media complex III and complex IV were formed below concentration levels of 1 x 10–3M of Sn (II) and of 3x 10–3M of HEDP. At high Sn (II)-HEDP concentrations complexes I and II were formed, while complexes III and IV were found at lower Sn (II)-HEDP concentrations in weak alkaline media. All four 99(m)Tc-HEDP complexes were stable against air oxidation until at least 6 hrs after preparation. Complexes I and II were stable against dilution by distilled water, while complexes III and IV were unstable and readily dissociated. In organ distribution studies high soft-tissue uptakes were observed with complexes III and IV, while complexes I and II had high bone-seeking properties.